User-Friendly Detention Pond Design Development Using Visual Basic 6.0 - Leong, Weng Chin (Universiti Sains Malaysia, 2005)
Nowadays, urban development in many developing countries, e.g. Malaysia, has found susceptible to adverse environmental crisis through excessive runoff that leads to the degradation of rivers and lakes. Therefore, this project has been carried out in which effective way to manage stormwater has to be developed. Actually, this project is focused more on the development of community and regional detention pond design using Visual Basic 6.0. In accordance with the guidelines provided in Urban Stormwater Management Manual for Malaysia ‘MSMA’ (DID, 2000), a computer model had been developed under this final year project. In other words, this model is built specifically to suit the design rainfall in Malaysia. Since the detention pond simulated via this design model is only to cater for large catchment area ( 80 ha and above ), hence, the Time-Area Method is proposed for the estimation of peak inflow and outflow. After attaining both the stage storage and stage-discharge relationships, Level Pool Routing will then be used in order to determine the peak discharge once a detention pond is designed. This is to ensure that the runoff discharged from the detention pond will not overflow the receiving water downstream. Even the manual calculation had been conducted to have this model checked and complemented. To verify its computation accuracy compared to spreadsheet (EXCEL), this model had been used to design the proposed wet community and regional detention pond located in a development area in Mukim 6, Daerah Seberang Perai Utara, P. Pinang. All the inflows, allowable outflows and required detention pond storage computed through this model were proved to be almost the same as that of EXCEL, only the outlet discharge is rather different between the two. As a whole, this model is indeed a helpful tool to do the preliminary design of wet detention pond.